Grammatical Errors in the Arabic Essay: Content Analysis Research on the Student of Arabic Language Education Department, Faculty of Languages and Arts, State University of Jakarta - Ahmad Marzuq (Universitas Negeri Jakarta, 2015)
This research is aimed to describing the gramatical errors on the text that committed by the students of Arabic Language and Literature Department, Faculty of Language and Arts, State University of Jakarta. Grammatical errors in this case covering morphological errors and syntactic errors. Data obtained through an Arabic essay writing activities performed by 25 students and then the data were analyzed using the method of error analysis. The results showed that 25 students essays founded 68 grammatical errors. These grammatical errors consist of 38 syntax errors and 30 morphological errors. Grammatical errors made by students can be caused by several factors such as the influence of the mother tongue / first, the influence of the second language being studied, as well as the influence of developmental errors.